Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Disrespect and Abuse During Childbirth in Tanzania: Are Women Living With HIV More Vulnerable? - Sando, David; Kendall, Tamil; Lyatuu, Goodluck; Ratcliffe, Hannah; McDonald, Kathleen; Mwanyika-Sando, Mary; Emil, Faida; Chalamilla, Guerino; Langer, Ana (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2014)
Introduction: HIV-related stigma and discrimination and disrespect and abuse during childbirth are barriers to use of essential maternal and HIV health services. Greater understanding of the relationship between HIV status and disrespect and abuse during childbirth is required to design interventions to promote women's rights and to increase uptake of and retention in health services; however, few comparative studies of women living with HIV (WLWH) and HIV-negative women exist. Methods: Mixed methods included interviews with postpartum women (n = 2000), direct observation during childbirth (n = 208), structured questionnaires (n = 50), and in-depth interviews (n = 18) with health care providers. Bivariate and multivariate regressions analyzed associations between HIV status and disrespect and abuse, whereas questionnaires and in-depth interviews provided insight into how provider attitudes and workplace culture influence practice. Results: Of the WLWH and HIV-negative women, 12.2% and 15.0% reported experiencing disrespect and abuse during childbirth (P = 0.37), respectively. In adjusted analyses, no significant differences between WLWH and HIV-negative women's experiences of different types of disrespect and abuse were identified, with the exception of WLWH having greater odds of reporting non-consented care (P = 0.03). None of the WLWH reported violations of HIV confidentiality or attributed disrespect and abuse to their HIV status. Provider interviews indicated that training and supervision focused on prevention of vertical HIV transmission had contributed to changing the institutional culture and reducing HIV-related violations. Conclusions: In general, WLWH were not more likely to report disrespect and abuse during childbirth than HIV-negative women. However, the high overall prevalence of disrespect and abuse measured indicates a serious problem. Similar institutional priority as has been given to training and supervision to reduce HIV-related discrimination during childbirth should be focused on ensuring respectful maternity care for all women.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Health providers’ opinions on provider–client relations: results of a multi-country study to test Health Workers for Change - Fonn, S; Mtonga, AS; Nkoloma, HC; Bantebya Kyomuhendo, G; Dasilva, L; Kazilimani, E; Davis, S; Dia, R (Health Policy and Planning, 2001)
A multi-centre study in four African countries was undertaken to test the acceptability and effectiveness of Health Workers for Change, a methodology to explore provider–client relations within a gender-sensitive context. This intervention addresses the interpersonal component of quality of care. The methodology, consisting of six workshops, was implemented by research teams in Zambia, Senegal, Mozambique and Uganda. It was found to be acceptable within in a range of cultural and primary health care settings. The workshops allowed difficult issues such as prejudice and bribery to be discussed openly, fostered problem solving and the development of practical plans to address problems that could strengthen district health systems.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde